Bortezomib down-regulates the cell-surface expression of HLA class I and enhances natural killer cell–mediated lysis of myeloma - Shi, Jumei (American Society of Hematology, 2008)
Human leukocyte antigen class I molecules expressed by tumor cells play a central role in the regulation of natural killer (NK) cell–mediated immune responses. The proteasome inhibitor bortezomib has demonstrated significant activity in multiple myeloma (MM). We hypothesized that treatment of MM with bortezomib results in the reduction of cell-surface expression of class I and thereby sensitizes MM to NK cell–mediated lysis. Here we report that bortezomib down-regulates class I in a time- and dose-dependent fashion on all MM cell lines and patient MM cells tested. Downregulation of class I can also be induced in vivo after a single dose of 1.0 mg/m(2) bortezomib. Bortezomib significantly enhances the sensitivity of patient myeloma to allogeneic and autologous NK cell–mediated lysis. Further, the level of decrease in class I expression correlates with increased susceptibility to lysis by NK cells. Clinically relevant bortezomib concentrations do not affect NK-cell function. Our findings have clear therapeutic implications for MM and other NK cell–sensitive malignancies in the context of both allogeneic and autologous adoptively transferred NK cells.